Strategi Meningkatkan Sikap Moderasi Beragama Di Kalangan Gen Z Dengan Pendekatan Filsafat Emmanuel Levinas Pada Prespektif Bahasa di Media Sosial - Abdul Ghoni Asror; Tommi Yuniawan; Imam Baehaqie (Faculty of Teacher Training and Education of Undaris, 2026)
Generation Z constitutes the largest age group in Indonesia, growing up as digital natives with unlimited access to social media, making them vulnerable to exposure to religious extremism and intolerance. This study aims to formulate strategies to enhance religious moderation among Gen Z through the lens of Emmanuel Levinas' philosophy, particularly from the perspective of language use on social media. Employing a descriptive qualitative method through in-depth interviews, observations, and literature review in Bojonegoro, Tuban, and Lamongan regencies, the study found that 73% of participants struggled to distinguish between constructive criticism and hate speech, while 34% had been exposed to intolerant content. The application of Levinas' concept of